Thermo-mechanical characteristics of spent coffee grounds reinforced bio-composites - Yanen, Cenk (Walter de Gruyter Gmbh, 2024)
This research examines the incorporation of spent coffee grounds (SCGs) into composite materials utilizing a three-part system composed of modified castor oil, polyester resin, and SCGs. The objective is to assess the mechanical, microstructural, and thermal characteristics of the resultant composites. The composite specimens underwent a thorough preparation and were tested through a battery of procedures comprising tensile testing, shore D hardness testing, SEM, FT-IR, and thermal conductivity measurements. Tensile testing revealed higher mechanical resilience, reinforcing the desirable properties of SCGs. The 5 % SCG-reinforced sample exhibited the highest tensile strength value, with a 41.85 % increase observed in comparison to the pure sample. The results of shore D hardness tests demonstrated that there was no significant change in material hardness up to 3 % additive content. However, a decrease in hardness was observed at higher additive rates. At a 7 % additive rate, there was a 2.82 % decrease in material hardness. Furthermore, the application of scanning electron microscopy (SEM) analysis has revealed the microstructural features of the composite matrix, which have highlighted the distribution of SCGs within it. The successful implementation of SCGs has also been verified by means of Fourier transform infrared (FT-IR) analysis. Finally, based on thermal conductivity measurements, it has been determined that SCGs are suitable for thermal insulation purposes. This study represents a significant contribution to the field of sustainable materials science, emphasising the potential benefits of SCGs in improving the effectiveness of composite materials.
Keywords: bio-composite; castor oil; polyester resin; spent coffee ground; thermo-mechanical